الخصوصيات الإبداعية في الصناعات التقليدية لدي سكان جزيرة جربة - الشابي, زهرة (المعهد العالي للتنشيط الشايي والثقافي, 2005)

تخريج أحاديث من مدونة أبي غانم بشر بن غانم الخراساني (من علماء أواخر القرن الثاني وبداية الثالث الهجري) بترتيب الشيخ القطب - المشايخي, ياسر بن سلطان بن حمد (كلية العلوم الشرعية, 2005)

تحقيق كتاب مناسك الحج للشيخ الجيطالي - الرزيقي, ناصر بن علي بن عبد الله (كلية العلوم الشرعية, 2005)

تخريج أحاديث من مدونة أبي غانم بشر بن غانم الخراساني (من علماء أواخر القرن الثاني و بداية الثالث الهجري) - السعدي, خميس بن هلال (كلية العلوم الشرعية, 2005)

فقه الإمام الربيع بن حبيب من خلال كتب الآثار إلى القرن السادس الهجري - اليعربي, سلطان بن سيف بن مهنا (كلية العلوم الشرعية, 2005)

سليمان باشا الباروني وآراؤه في الإصلاح السياسي والفكري - المعولي, يوسف بن يعقوب بن صالح (كلية العلوم الشرعية, 2005)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

مواقف الجزائريين من التجنيد الإجباري 1912-1916 - ناصر, بالحاج بن باحمد (المدرسة العليا للأساتذة في الأدب و العلوم الإنسانية, 2005)
Keywords: Service militaire obligatoire‎ -- Mzab -- période coloniale

من جوابات الإمام أفلح بن عبد الوهاب - فخار, عمر بن الحاج (معهد العلوم الشرعية, 2005)
Keywords: الأحكام (فقه إسلامي)

نماذج من آليات تداول الموروث الموسيقى بجزيرة قرقنة فرقة الصغار نموذجا - بن فرجاني, حنان (المعهد العالى للموسيقى, 2005)

مدخل إلي البحث في المميزات التعبيرية لموسيقى الإنشاد الديني سيد شطا نموذجا - شطورو, محمد حسان (المعهد العالى للموسيقى, 2005)

وجد وأسى ديوان الشيخ إبراهيم بن بحمان ابن ابي محمد بن عبد الله بن عبد العزيز الثميني اليسجني المصعبي المتوفي 1232هـ/1817م تفديم تحقيق وتعليق - حاج أمحمد, يحيى بن بهون (جامعة الجزائر, 2005)
Keywords: Biographies -- Mzab -- 19e siècle

الشيخ أبو اليقظان إبراهيم ابن الحاج عيسى وقضايا عصره (1306هـ-1888م)*(1393هـ-1973م) - بن رحال, يمينة (المدرسة العليا للاداب والعلوم الانسانية, 2005)
Keywords: Abū ‘l-Yaqẓān, Ibrāhim (1888-1973)

La coiffure noire: signe d'identité - Mohamadi, Cécile (Université Paris 8, 2005)

L'implantation du mouvement national algérien en Kabylie entre les années 1920 et 1950 - Dekkal, Saïd (Université Paris 8, 2005)

La littérature orale berbère: la tradition orale de Kabylie - Touati, Rachida (Université Paris 8, 2005)
Keywords: Littérature -- Kabylie

La Nation de l'Islam aux Etats-Unis - Toumi, Najiba (Université Paris 8, 2005)

La confrérie Aïssawa - Korch, Rachida (Université Paris 8, 2005)

La vie quotidienne chez les Ottomans de XVe siècle jusqu'au XVIIIe siècle - Cihangir, Ceren Sabahat (Université Paris 8, 2005)

Le développement communautaire à la Grande Comore - Barwane, Ibrahim (Université Paris 8, 2005)
Keywords: Développement local -- Comores

Togo : De la démocratie coloniale des années 60, renouveau démocratique des années 90 (1960-1990) - Togbe, Komlan Ablam (Université Paris 8, 2005)

Réflexion sur l'objectivation de l'écriture de l'histoire en Afrique de l'Ouest : entre tradition orale et recherche scientifique le cas de l'empire médiéval du Mali - Gout, Antoine (Université Paris 8, 2005)

Une relation qui s'établit entre les déplacés et les institutions en Colombie - Ramirez Leon, Diana Constanza (Université Paris 8, 2005)

Le suicide des femmes en Chine rurale - Fisson-Blackwell, Violaine (Université Paris 8, 2005)

Monographie des Ouled Nail - Yakout, Aïcha (Université Paris 8, 2005)

Au cinéma, un rapport magique entre le spectateur et le film - Karam, Sofia baptista (Université Paris 8, 2005)

Le patrimoine immatériel, nouvelles réalités, nouveaux enjeux - Yelles-Chaouche, Feriel (Université Paris 8, 2005)
L'HISTOIRE ET LA GEOGRAPHIE ONT FAIT DE LA REGION ORIENTALE L'UNE DES REGIONS LES PLUS ORIGINALES ET LES PLUS PARADOXALES DU MAROC. SON ORIGINALITE EST DUE PRINCIPALEMENT A SON ISOLEMENT RELATIF PAR RAPPORT AUX GRANDS CENTRES DE DECISION ECONOMIQUE ET POLITIQUE DU MAROC. SON CARACTERE PARADOXAL LUI VIENT DE SA SITUATION DE REGION FRONTIERE. LE PROBLEME D'INTEGRATION DE LA REGION ORIENTALE EST POSE AUJOURD'HUI AVEC PLUS D'ACUITE QUE PAR LE PASSE. NOUS EXAMINONS ICI LES RAISONS ET LES FACTEURS TANT STRUCTURELS QUE PUREMENT GEOPOLITIQUES QUI JUSTIFIENT LE NOUVEL INTERET DONT LA REGION ORIENTALE SEMBLE FAIRE L'OBJET ACTUELLEMENT.

La situation économique et agricole du pays Senoufo au Mali : cas du village de Loulouni - Keïta, Abdoulaye (Université Paris 8, 2005)

L'exclusion sociale : entre résistance et soumission - Strauss, Jean-Paul (Université Paris 8, 2005)

Les règles implicites de la société rwandaises et leurs impacts sur le développement social et politico-économique de 1898 à 1994 - Bakunda Isahu Cyicaro, Pierre-Célestin (Université Paris 8, 2005)
La haine inter-ethnique au Rwanda est issue des représentations sociales construites par les Rwandais eux-mêmes. La société rwandaise est fondée sur des valeurs explicites et occultes. Ce mélange entraîne, chez tout un chacun, au Rwanda, une quasi double personnalité. L'homme Rwandais devient ondoyant, perd la logique de la transparence au profit de ses propres intérets et opte pour " le travestissement de la vérité " ou le mensonge. Il instaure un système où les règles implicites vont générer le clientélisme et la corruption dans une société hiérarchisée. L'arrogance et le mépris des uns suscitent la méfiance des autres ; le manque de tolérance et de patience cède la place à la haine, véritable frein du développement socio-économique et vecteur destructeur de la société. Même la civilisation occidentale, à travers l'enseignement, n'aura pas d'influence sur la personnalité des Rwandais et ne pourra ni transformer sa mentalité ni modifier son regard aussi bien jaloux que haineux à l'égard de l'autre. Au contraire, la présence occidentale va accentuer la division inter-rwandaise en classant les uns de façon plus favorable sur l'échelle sociale pour dominer les autres et en instaurant une administration indirecte. Ainsi, les feux de la haine sont davantage activés entre Hutu et Tutsi jusqu'aux atrocités de 1959 à 1967 et de la guerre d'octobre 1990 ; celle-ci conduit à l'innommable tragédie d'avril 1994 et aux représailles consécutives durant plusieurs années.

تحقيق كتاب اختصار المواريث والفرائض للشيخ أبي عمار عبد الكافي الوارجلاني رحمه الله ت: فبل 570 هـ - كمارا, عمر بن كرامغ (معهد عمي سعيد, 2005)
Keywords: Fiqh -- traité -- 12e siècle

Les villages bobo-dioula, du commerce musulman à la culture rentière du coton - Phliponeau, Marie (Université Paris 8, 2005)

Oman's foreign policy : foundations and practice - Khalili, Majid al- (Florida International University, 2005)

Islam and Arabism in Zanzibar: The Omani Elite, the Arab World and the Making of an Identity, 1880s-1930s - Ghazal, Amal N. (University of Alberta, 2005)
Keywords: Zanzibar

The Origin and Development of the Ibadi Imamate Ideal - Gaiser, Adam R. (University of Virginia, 2005)
Keywords: Imamat -- Ibadisme

Etude floristique et nutritive des parcours camelins du sahara septentrional algérien : cas des régions de Ouargla et Ghardaia - Chehma, Abdelmadjid (Université Badji Mokhtar, 2005)
Keywords: Botanique -- Mzab

Monks, Martyrs and Mujahidin: Militant Piety in Late Antiquity and Early Islam - Sizgorich, Thomas N. (University of California, 2005)

The Role of The Woman in Al-Kawarij - Samara’ee, Hind Yousif Majeed Al- (University of Tikrit, 2005)
The role of the woman in “Al-Khawarij” movement was unlike the role of any other woman in any other movement , Party or human community as the woman here had left clear fingerprints in the history of “Al-Khawarij” politically , ideologically and in military contribution . This contribution was an active reason behind the continuation of this movement for long . This role handled by the Kharijiite woman had not emerged in a vacuum . Her mentally deep – rooted belief in herself made her response positively to this movements needs practicing alive participation which offered her absolute liberty , a type of participation which could not be compared by any woman in any other movement . The woman was not forced to do things she rejected , and through this participation several life roles were created which had been played with unlimited distinction at all levels : in politics , army , literature and ideology . In some cases she appeared as a decisive fighter in the battles carrying her sword fighting the enemies with bravery like a lion on a prey , in other cases , she led the Kharijiite men and women in the battlefields ; besides , the Khawarij had permitted the Imama of a woman and even having a position of a caliph whose duty was leading the armies at the time of the wars . The woman had the role of nursing as well gaining this position through her effect on men with high efficiency . There was , however , on better evidence of the caliph , Ali Bin abi Talib , who was medically treated by a Kharijiite woman . A Kharijiite woman shwed a political rejection of some trends in the movement , and sometimes she manifested her dissatisfaction of the movement’s beliefs in preventing the men to go to wars for fear of facing death to keep her family safely united . The Kharijiite woman was a figure of power and a good communicator . She usually had talks and discussions with the caliphs and rulers expressing her opinion freely without fear or hesitation and this represented her great challenge , conceit and courageous attitude in speech . The Kharijiite woman , however jeopardized herself for the sake of the ideology in which she believed. Sometimes she nobly allowed to receive the adherents (followers) of the Kharijiite thought in the Arab Eastern lands holding secret meetings and sessions in her house so that they might be far off the caliph’s eyes and detectives . In this case the movement was protected against various sorts of dangers ; in this way , the movement remained united and could circulate its principles every where. Concerning the literary and ideological attitdes , so many Kharijiite women had experience in producing poetry distinctively , in that she was equal to men which reflected her innovative aspects by using enthusiastic verses to encourage the men to fight bitterly and take revenge for the dead . the Kharijiite poetesses were sophisticated in expressing novel feelings towards the dead. The status of a woman in the literature of this movement was depicted as a symbol for love , struggle and inspiration as in that of men’s poems and lives . its apparent that the Kharijiite woman made an important part in both states of Abaddhiya and Midreriya in the Arab Magrib politically , religiously , scientifically , culturally , and economically . She was a politician , a scientist inviting scientists in her house , a theologian knowing the Islamic canons , a wise woman consulted by rulers and commanders in their political affaires giving her opinions out of deep experience in life , a good housewife at home and a hard worker in farms . She was a good dressmaker and having a big ability in manufacturing neatly – knitted carpets . Finally , the Kharijiite woman affected others in her community and was affected by the theological judgements coming from the Kharijiite judges . Some judgements decided by Al-Khawarij permitted her to hold a position of Imama and leadership although she was some times oppressed by some judgments as forcing her to marry a man of close kinship rather than a man of her choice and this tradition is frankly forbidden by the massage of Islam . And all this had its negative influence on the woman herself , the family and the community . It is concluded that the Kharijiite woman had actually been the master of her age (era) obtaining a historic status which she deserved in the Islamic Arab history and even in the political , military and ideological history of Al-Khawarij.
Keywords: Kharijisme

La professionnalisation de la mort musulmane en France : enquête de terrain auprès des pompes funèbres musulmanes - Kebir, Samia (Université Paris 8, 2005)

حكم مرتكب الكبيرة عند الإباضية المعاصرين: عرض ونقد - الشهراني, أسعد بن سعيد (جامعة أم درمان الإسلامية, 2005)

Wajd wa Asā : Dīwān al-Shaykh Ibrāhīm b. Biḥmān Abī Muḥammad b. ʿAbd Allāh b. ʿAbd al-ʿAzīz al-Thamīnī al-Yasjanī al-Muṣʿabī al-Mutawafā 1232 h/1817 m : Taqdīm Taḥqīq wa Taʿlīq - Ḥajj Amḥammad, Yaḥyā b. Buhūn (Université d'Alger, 2005)
Keywords: Poésie -- Mzab

Les bains d'Alger durant la période ottomane (XVIe-XIXe siècle) : histoire, topographie et étude urbaine - Cherif-Seffadj, Nabila (Université Paris-Sorbonne, 2005)

الالات الإيقاعية الشعبية بجزيرة جربة الة الطبل نموذجا - بن عيسى, أمين (2005)
Keywords: Musique -- Djerba

الامامة في عمان 1954-1973 م: دراسة تاريخية - الشحي, عبد الله علي (جامعة الدول العربية, 2005)

سير الوسياني :‏ ‏دراسة المجموعة وتحقيق الجزء الأول منها - بوعصبانة, عمر بن لقمان (‏جامعة الأميرعبد القادر, 2005)
Keywords: Prosopographie -- Afrique du Nord

شعر الخوارج: دراسة أسلوبية - الصميدعي, جاسم محمد (جامعة الانبار, 2005)
Keywords: Poésie kharijite

دور المرأة في حركة الخوارج - السامرائي, هند يوسف مجيد (جامعة تكريت, 2005)
Keywords: Kharijisme

موقف المستشرقين من الافتراق والفرق (الخوارج والشيعة) : عرض ونقد - السلوم, مسفر بن سعيد بن علي (جامعة الإمام محمد بن سعود الإسلامية, 2005)
Keywords: Kharijisme

الولاية والبراءة عند الإباضية: المفاهيم والآثار - الهاشلي, يحيى بن سالم بن خلفان (جامعة الزيتونة, 2005)

Centre de stages de préparations sportives à Djerba - Ben Jemaa, Rached (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2005)
Keywords: Architecture -- Djerba

Un Ecomusée à Djerba : Espace de sensibilisation et d’Education Environnementale - Ben Haj, Lotfi (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2005)
Keywords: Architecture -- Djerba

Nouvelle interprétation de l’espace Scolaire : Lycée à Djerba - Makaiz, Kamel (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2005)
Keywords: Architecture -- Djerba

Aménagement de Borj Ghazi Mustapha de l’île de Djerba en un musée archéologique - Ourir, Leila (Institut Supérieur des Beaux-Arts de Tunis, 2005)
Keywords: Architecture -- Djerba

Ecole de formation artisanale à Djerba - Satouri, Rym (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2005)
Keywords: Architecture -- Djerba

Caractéristiques environnementales et dynamique littorale de la plage d’Aghir à Jerba - Zekri Harrabi, Faten (Faculté Des Sciences de Sfax, 2005)
Keywords: Littoraux -- Djerba

Etude d’un modèle de sédimentation littorale actuelle active: Cas de la flèche littorale Ras R’mel au nord de Jerba - Khlifi, Imed (Faculté Des Sciences de Sfax, 2005)
Keywords: Littoraux -- Djerba

Analyse de la composition minérale de différents cultivars de palmier dattier de l’ile de Djerba - Moussa, Majida (Institut Supérieur des Etudes Technologiques, 2005)
Keywords: Botanique -- Djerba

Biodiversité des milieux insulaires. Étude de cas: l’île de Djerba - Zarrouk, Anis (Institut national agronomique de Tunis, 2005)

la variété de pommier douce de Djerba : caractérisation chimique et essais de culture in vitro - Boudabous, Manel (Université de Tunis El Manar, 2005)
Keywords: Botanique -- Djerba

Typage du marqueur biallélique (M207) au niveau du chromosome Y chez un groupe de population de l’île de djerba - Alouane, Dorra (Institut supérieur des technologies médicales de Tunis, 2005)
Keywords: Génétique -- Djerba

Island Colonisation and Abandonment in Mediterranean Prehistory - Dawson, Helen Sarah (University College, 2005)
Keywords: Archéologie -- Djerba